2019
DOI: 10.1101/731281
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of Candida auris infection in a neutropenic murine model

Abstract: Candida auris has become a global public health threat due to its multidrug resistance and persistence in hospital and nursing home settings. Although a skin colonizer, C. auris can cause fatal bloodstream infections and most patients succumb to multi-organ failure. Currently, there are limited animal models to study the progression of C. auris infection. Here we compare two murine models of neutrophil depletion using monoclonal antibodies 1A8, anti-Ly6G+ and RB6-8C5 anti-Ly6G+-Ly6C+. We also compare inoculums… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 41 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…Within each clade, isolates may have differences in morphology, levels of virulence, growth rates, and antifungal-resistance profiles [ 4 , 32 ]. Being so, in preparation for our animal studies, we first investigated the antifungal susceptibility of two clinical isolates of C. auris belonging to distinct clades: AR-0386 (CAU-06) of Clade IV and AR-0389 (CAU-09) of Clade I. AR-0386 is a highly aggregative South American isolate that has been shown to be less virulent than C. albicans in mouse models [ 33 ], while AR-0389 is a nonaggregative South Asian isolate that is highly virulent in mouse models [ 31 , 34 ]. It has been reported that nonaggregating C. auris isolates such as AR-0389 are among the most virulent clinical isolates, with virulence comparable to that of C. albicans in the invertebrate Galleria mellonella model [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Within each clade, isolates may have differences in morphology, levels of virulence, growth rates, and antifungal-resistance profiles [ 4 , 32 ]. Being so, in preparation for our animal studies, we first investigated the antifungal susceptibility of two clinical isolates of C. auris belonging to distinct clades: AR-0386 (CAU-06) of Clade IV and AR-0389 (CAU-09) of Clade I. AR-0386 is a highly aggregative South American isolate that has been shown to be less virulent than C. albicans in mouse models [ 33 ], while AR-0389 is a nonaggregative South Asian isolate that is highly virulent in mouse models [ 31 , 34 ]. It has been reported that nonaggregating C. auris isolates such as AR-0389 are among the most virulent clinical isolates, with virulence comparable to that of C. albicans in the invertebrate Galleria mellonella model [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…A/J mice are deficient in complement protein C5 and its cleaved product C5a, a pro-inflammatory chemoattractant important for anti- Candida protection [ 28 , 29 , 30 ]. This renders A/J mice highly susceptible to C. auris disseminated infection without the need for immunosuppressive drugs [ 31 ]. Using this model, we identified three mAbs that provided significant protection, as evidenced by extended survival and lower fungal burdens in the kidney, brain, and heart, compared to control mice.…”
Section: Introductionmentioning
confidence: 99%